Efectividad de fertilizantes arrancadores fosfatados sobre la productividad del maíz amarillo duro en el valle del Río Carrizal - Alcívar Mera, Daniel Eduardo (2018)
The objective of the research was to evaluate the effectiveness of several phosphate fertilizers applied as starters on the productivity and profitability of hard yellow corn in Carrizal river valley. The experiment was carried out at Escuela Superior Politécnica Agropecuaria de Manabí “Manuel Félix López”. Seven treatments were evaluated: Diammonium Phosphate (DAP), Mono Ammonium Phosphate (MAP), MicroEssential SZ (MESZ), 15-15-15 and 10-30-10, all cast as starters on the side and under the seed. In order to contrast the effectiveness of the starter fertilizers, a conventional control based on the MESZ fertilizer placed in the surface band at the emergence of the seedlings was included, and a control with omission of P. A randomized complete block design was used. Seven treatments and three replicas, with a total of 21 experimental units. The main variables evaluated were the yield (qq ha-1) and the net economic benefit. The results showed that the MicroEssentials SZ fertilizer (MESZ) placed as a starter on the side and below the seed obtained the highest yield with 256 qq ha-1, in contrast to the other starter phosphate fertilizers and conventional control treatments with 220 qq ha- 1 and omitting P with 132 qq ha-1. Similarly, the treatment based on MESZ placed as starter was the one that obtained the highest net benefit with 1620 USD ha-1, since it obtained the highest increase in yield and lowest increase in costs that vary in relation to the other treatments evaluated as starters and control treatments.